Quimioterapia y/o radioterapia en pacientes con cáncer gástrico resecables o potencialmente curativos. Visión de cirujanos. - Csendes J., Attila; Castillo K., Jaime (Revista Hospital Clínico Universidad de Chile, 2011)
The management of patients with advanced gastric carcinoma who are candidates to surgical resection, implies the use of additional adyuvant or neo-adyuvant treatments. The present article reviews briefly the results of different treatments. The best results up to now have been obtained with the use of quemotherapy plus radiotherapy after surgical resection (Mac Donald´s protocol) or with the use of preop and postoperative quemotherapy (Cunningham´s protocol). Patients candidates to such treatments correspond to cases with resected gastric cancer, with tumoral infiltration up to the serosa to extra serosa infiltration and those who have 1 or more metastatic lymph nodes. There are several new treatment protocol, which must be evaluated by prospective and randomized studies.